Intraprocedural PRAETORIAN score for early assessment of S‐ICD implantation: A proof‐of‐concept study. (5th October 2021) - Gasperetti, Alessio; Schiavone, Marco; Biffi, Mauro; Casella, Michela; Compagnucci, Paolo; Mitacchione, Gianfranco; Angeletti, Andrea; Vogler, Julia; Proietti, Riccardo; Ziacchi, Matteo; Dello Russo, Antonio; Natale, Andrea; et al.
Abstract: Introduction: The PRAETORIAN score (PS) was developed to assess the implant position and predict defibrillation success of the subcutaneous implantable cardioverter defibrillators (S‐ICD). The main critique moved to the routine use of PS has been its postprocedural timing, that limits its usefulness on procedure guidance. The aim of this proof‐of‐concept study was to assess the feasibility of an intraprocedural use of PS. Methods: Forty consecutive patients undergoing S‐ICD implantation were enrolled. Intraprocedural PS (IP‐PS) obtained with fluoroscopy before closure of the pocket and postprocedural PS (PP‐PS) obtained with two‐views chest X‐ray were compared. Intraprocedural data and PS were compared with the historic cohorts of the involved institutions. Results: When assessing IP‐PS and PP‐PS, a complete overall agreement was observed (100%, 1.00‐ κ; p < .001). When assessing a per‐step agreement, a very high‐degree of concordance in evaluating Step 1 of the PS was observed (95%, 0.81‐ κ; p < .001). A complete agreement in Step 2–3 (100%, 1.00‐ κ; p < .001) of the PS was reported. In comparison with our historical cohort, procedural time in the IP‐PS cohort did not increase (45 [41–52] vs. 45 [39–49] min; p = .351) while the expected increase in fluoroscopy time resulted scarce (15 [10–15] s). Conclusion: An IP‐PS can be reliably obtained using fluoroscopy guidance during S‐ICD implantation, without a significant increase in procedural duration and may serve as guidance for implanting physicians, to avoid postprocedural S‐ICD repositioning, leading to patient discomfort and significantly enhancing infective risks. IP‐PS showed a very high agreement with the PP‐PS obtained from two‐views chest X‐ray.